Tower houses and the maritime economy c.1400-1641 : a County Down case study - McAlister, Victoria Louise (Trinity College (Dublin, Ireland). Department of History, 2012)
This thesis investigates how the population interacted with, and contributed to, the maritime economy by looking at three baronies in coastal County Down. It utilises tower houses and associated settlements as a medium through which to examine these interactions. Therefore the tower houses are not viewed in isolation, the research is instead a study of settlement, and the role of buildings within settlements. The primary motivation of this thesis is to identify the extent of a commercial orientation within the tower houses of coastal County Down, in terms of their function and location. Both archaeological and historical sources are used to reconstruct these commercial interactions and to examine how the maritime economy changed over time. In this latter area attention has more specifically been focussed on whether economic change was cause for the cessation of construction of the building type in the seventeenth century.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin